2016
DOI: 10.1038/srep24855
|View full text |Cite
|
Sign up to set email alerts
|

The chemopreventive potential of lycopene against atrazine-induced cardiotoxicity: modulation of ionic homeostasis

Abstract: People who drink water contaminated with atrazine (ATR) over many years can experience problems with their cardiovascular system. Lycopene (LYC) has been shown to exhibit cardiovascular disease preventive effects. However, chemopreventive potential of LYC against ATR-induced cardiotoxicity remains unclear. To determine the effects of ATR and/or LYC on heart, mice were treated with ATR (50 mg/kg or 200 mg/kg) and/or LYC (5 mg/kg) by intragastric administration for 21 days. Histopathological and biochemical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 57 publications
3
43
0
Order By: Relevance
“…Moreover, they exert important influence in regulating the transmembrane ionic balance to maintain proper function of the vasculature [35, 36]. The previous investigations demonstrated that high temperature inhibited the mitochondrial Ca 2+ -ATPase activity in broilers [38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they exert important influence in regulating the transmembrane ionic balance to maintain proper function of the vasculature [35, 36]. The previous investigations demonstrated that high temperature inhibited the mitochondrial Ca 2+ -ATPase activity in broilers [38].…”
Section: Discussionmentioning
confidence: 99%
“…So the global researchers are mainly concerned and interested in studying the adverse effects of ATR in the wildlife and experimental animals . Furthermore, most of these studies evaluated the effects of ATR exposure in cell, tissue and organs . However, only a few studies investigated the mechanisms of the hepatotoxicity of ATR exposure in quails.…”
Section: Discussionmentioning
confidence: 99%
“…35 Furthermore, most of these studies evaluated the effects of ATR exposure in cell, tissue and organs. 36,37 However, only a few studies investigated the mechanisms of the hepatotoxicity of ATR exposure in quails. In this study, we indicated that the toxicity effects of ATR on the liver through activating nuclear xenobiotic receptors responses and ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…This protective effect has been suggested to be exerted via regulation of the ionic homeostasis disorder through modulation of ATPase activity and subunits (1a1, 1b3, 1b4, and 2b4) transcription [76]. Moreover, similar studies have reported the potential protective effect of lycopene (5 mg/kg, orally, for 21 days) against atrazine (50 or 200 mg/kg, orally, for 21 days) stimulated cardiotoxicity in a mouse model [77]. Nan Li et al showed that supplementation of mice with lycopene regulated NO production, inactivated the Tumor necrosis factor receptor-associated factor 6 (TRAF6-NF-kB) pathway as well as up-regulated TNF-α, IL-6, cyclooxygenase 2 (COX-2), and IL-1β and down-regulated the transforming growth factor beta 1 (TGF-β) [78].…”
Section: Atrazinementioning
confidence: 82%
“…This protective effect has been suggested to be exerted via regulation of the ionic homeostasis disorder through modulation of ATPase activity and subunits (1a1, 1b3, 1b4, and 2b4) transcription . Moreover, similar studies have reported the potential protective effect of lycopene (5 mg/kg, orally, for 21 days) against atrazine (50 or 200 mg/kg, orally, for 21 days) stimulated cardiotoxicity in a mouse model . Nan Li et al .…”
Section: Chemical Induced Toxicitymentioning
confidence: 90%